If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * log(a) + -1x * log(b) + x * log(c) = log(b) + 3log(c) Multiply x * glo glox * a + -1x * log(b) + x * log(c) = log(b) + 3log(c) Multiply glox * a aglox + -1x * log(b) + x * log(c) = log(b) + 3log(c) Multiply x * glo aglox + -1glox * b + x * log(c) = log(b) + 3log(c) Multiply glox * b aglox + -1bglox + x * log(c) = log(b) + 3log(c) Multiply x * glo aglox + -1bglox + glox * c = log(b) + 3log(c) Multiply glox * c aglox + -1bglox + cglox = log(b) + 3log(c) Multiply glo * b aglox + -1bglox + cglox = bglo + 3log(c) Multiply glo * c aglox + -1bglox + cglox = bglo + 3cglo Solving aglox + -1bglox + cglox = bglo + 3cglo Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'bglox' to each side of the equation. aglox + -1bglox + bglox + cglox = bglo + bglox + 3cglo Combine like terms: -1bglox + bglox = 0 aglox + 0 + cglox = bglo + bglox + 3cglo aglox + cglox = bglo + bglox + 3cglo Add '-1cglox' to each side of the equation. aglox + cglox + -1cglox = bglo + bglox + 3cglo + -1cglox Combine like terms: cglox + -1cglox = 0 aglox + 0 = bglo + bglox + 3cglo + -1cglox aglox = bglo + bglox + 3cglo + -1cglox Divide each side by 'glox'. a = bx-1 + b + 3cx-1 + -1c Simplifying a = bx-1 + b + 3cx-1 + -1c Reorder the terms: a = b + bx-1 + -1c + 3cx-1
| 1/2(7y-1)+1/4(6y+5)= | | 7a-5+2a= | | z=0.36 | | graphx+y=5 | | 5*x=2 | | (2*x^2)+8x+7= | | 2*-3-3*y=9 | | x^3+x^2+5x+5=0 | | 2*x^2+8x+7= | | (x^3+3x^2+7)+(3x^3-4x^2-5x+1)= | | 4x^2=.506 | | -3p+7=5-(7p+7) | | -4(t-2)+7t=8t-3 | | 4b-2(b-9)=2+3b | | 6(y-1)=2y+18 | | 2*x^2+10x+2=0 | | 81y^4-72y^2+16=0 | | 8ln(7x)=16 | | -9x-208=55+2x | | 2y+8z=-32 | | -x-62=10x+92 | | 14=x-30 | | 46+m=16 | | 8x-y+3z=20 | | n+27=-60 | | -25x+2x=4x+15 | | x-38=18 | | 3X^2+12X-33=0 | | 0.375z+1=3 | | -6x-198=3x+63 | | 9a-2ab-6-9ab+4a= | | (2x^2)-6x-15=0 |